(untitled) (Altre Modernità, 2014)
Two of the most widely represented and recognisable cultural examples of the gaze that spies are the supernatural and/or divine eye, which in religious, mythical and tragic narratives seeks and punishes those who misbehave, and on the other hand the controlling, pervasive gaze of technological surveillance, which is typical of modern institutional apparatuses. This essay aims to analyse the ways in which a highly sophisticated, postmodern graphic novel, Neil Gaiman’s The Sandman (1989), elaborates precise representational strategies in order to blend, metaphorize and then deconstruct the aforementioned narratives of control; in the 2000-page fantasy bildungsroman, mythological, pagan and literary elements are combined to shape the Eumenides, a tripartite deity of vengeance which is represented as pure, abstract gaze, and whose inescapable duty is to punish those who act against nature; however, a complex articulation of the concepts of agency and responsibility manages to undermine the ideological foundation of such essentialism, in order to negotiate forms of resistance against vigilance which revolve around the very necessity of the gaze. Michael Foucault’s works about Panopticism, and especially the relationship between power and control provide the theoretical background for such examinations.